Vance Bioenergy Sdn Bhd / Muhammad Asyraf Mat Nawi - Mat Nawi, Muhammad Asyraf (Faculty Of Chemical Engineering, 2021)
The company, Vance Bioenergy Sdn. Bhd, not only give a great working experience, but also give a warmth welcome and a good working environment. The engineers in the plant teach many new things and give exposure of a whole new engineering world to the trainee. The deepest gratitude would like to be express to the greatest production department, starting with the Head of Department, also the trainee's supervisor, Mr. Faizal Lammappa, follow with production engineers, the trainee's mentor, Mr. Syamim, Mr. Farid, Mr. Zulkifli and Ms. Siti for their unwavering dedication in sharing their knowledge and experiences despite their busy schedules, giving an endless support, guidance and lastly providing great hospitality along the way. Through the production department, the trainee able to exercise all the theories and practices that being taught during the diploma. The sincerest gratitude also being express to the industrial training coordinators, Mr. Mohd Haikal Mustafa and Ms. Noor Hidayu Abdul Rani, for their infinite effort in ensuring the internship is done perfectly and commitment in guiding the students from zero knowledge prior to industrial training until the students gain great working experiences. The trainee also earnestly happy to be able to contribute to the company with the given tasks and mini project even though it only a miniscule accomplishment. Universiti Teknologi Mara, UiTM also able to achieve its goal in producing a well-rounded students which not only have great leadership skill, grandiloquent in communicating with excellent academic performance, but also has an experience of working in the respective industry which can help students to get the upper hand for the future endeavors in overcoming their hardship when starting to work in engineering world. Many benefits and knowledge gain prior to this industrial training and give the students the better understanding on respective course industry.